IMPACT OF LAND USE AND LAND COVER (LULC) CHANGES ON FLOOD RISK IN THE DOWNSTREAM COMMUNITIES OF THE TIGA DAM, KANO RIVER, NIGERIA - Balarabe, Abdullahi; Iguisi, E. O.; Mukhtar, Ibrahim; Lawal, Z. R.; Ahmed, Abdulrazak; Umar, Jibril Haruna; Salihu, Suleiman Adoga; Hassan, Abdulhakim Wagini; Haliru, Y.; Aliyu, M. H.; Khalid, Usama Salisu (FUDMA JOURNAL OF SCIENCES, 2025)
Landuse and land cover (LULC) changes significantly influence hydrological systems, especially in semi-arid regions where such changes amplify flood risks. This study examines the spatiotemporal dynamics of LULC between 2009 and 2023 and their implications for flood risk in downstream communities of the Tiga Dam, Kano State, Nigeria. Using remote sensing and Geographic Information System (GIS) techniques, the analysis reveals a notable decline in shrubland cover from 50.57% in 2009 to 43.33% in 2023, alongside an increase in agricultural land from 19.81% to 23.04%. These changes reflect substantial vegetation loss and land conversion, which have increased surface runoff and reduced infiltration. Hydrological modeling confirms that urban expansion and deforestation have intensified both the frequency and severity of floods in the region. Projections based on current trends indicate continued vegetation degradation and urban sprawl by 2050, elevating future flood risks. The findings underscore the urgent need for sustainable land management practices, including afforestation, conservation agriculture, and effective land-use regulation. Furthermore, integrating geospatial data with hydrodynamic modeling provides critical insights for identifying flood-prone zones and designing risk mitigation strategies. This study highlights the importance of evidence-based, proactive land-use planning to strengthen climate resilience and reduce flood vulnerability. As climate variability and human pressures persist, targeted interventions are crucial to safeguard lives, livelihoods, and infrastructure in vulnerable floodplain areas.